A flexibilização das leis trabalhistas no Brasil como pressuposto para o desenvolvimento econômico do país - Reis, Amanda Madeira (2017)
Economy and work have always been linked. Since the Industrial Revolution, with the replacement of man by machine, the labor market is undergoing profound changes. The competitiveness in the international market, increasingly fierce, requires countries an attitude change with regard to its legislation in order to adapt to these changes and are able to develop themselves economically and socially, ensuring quality of life for its citizens. The Brazilian state, capitalist, with social and neoliberal welfare policies need to review its labor laws, created in the era Vargas and fascist bias, extremely patronizing, so that it is not an obstacle to the economic development of the country, before the new reality imposed by globalization. With the protective order, sometimes the Brazilian labor laws generate helplessness to the poorest and most needy. economically developed world markets are unbureaucratic and there is a flexibility for hiring and firing. In many respects employee and employer is to decide what is more favorable, and not the state.